Business as mission : a comprehensive guide to theory and practice - Johnson, C. Neal, 1942-; Rundle, Steve, 1959- (Downers Grove, Ill. : IVP Academic, 2009)
Business as mission (BAM) is a mission strategy whose time has come. As global economics become increasingly interconnected, Christian business people and entrepreneurs have unanticipated opportunities to build kingdom-strategic business ventures. But Christian companies and business leaders do not automatically accomplish missional purposes. BAM requires mastery of both the world of business and the world of missions, merging and contextualizing both into something significantly different than either alone. C. Neal Johnson offers the first comprehensive guide to business as mission for practitioners. He provides conceptual foundations for understanding BAM's unique place in global mission and prerequisites for engaging in it. Then he offers practical resources for how to do BAM, including strategic planning and step-by-step operational implementation. Drawing on a wide variety of BAM models, Johnson works through details of both mission and business realities, with an eye to such issues as management, sustainability and accountability. Business as mission is a movement with enormous potential. This book breaks new ground in how faith and work intersect and are lived out in crosscultural contexts, where job creation and community transformation go hand in hand. Come, participate in what may well be one of the most strategic mission paradigms of the 21st century. - Publisher
What is business as mission? -- BAM models -- BAM's place in the sun -- Four camps : section 1 -- Four camps : section 2 -- BAM's basic beliefs -- BAM's biblical roots -- BAM : personal prerequisites -- BAM : corporate prerequisites -- Stages of BAM development -- Levels of faith integration and accountability -- BAM's multiple bottom lines -- Kingdom impact -- Writing the BAM plan -- The functional analysis approach : section 1 -- The functional analysis approach : section 2 -- People and money -- How to do BAM : steps 1-8 -- How to do BAM : steps 9-15 -- Macroeconomic issues -- Political issues -- Spiritual and mission issues -- Business-specific issues -- Expatriate issues -- Epilogue : the next generation
Includes bibliographical references and indexes
Keywords: Business enterprises -- Religious aspects; Mission statements; Missions